Design and Build a Population Administration Data Collection Application System Using the Zachman Framework - Anti Aprianti; Yayatillah Rubiati; Muhamad Renaldi Aripin; Cecep Warman (Nusa Putra University, 2021)
The purpose of this study is to determine how the application of the Zachman Framework in designing a population administration data collection system in Kadaleman village, because the current process is still carried out conventionally so that data storage is irregular. In analyzing the system using the Zachman Framework approach with a Planner, Owner, Designer, and Builder perspective and perspective issues, namely What, How, Where, Who, and When. For system modeling using UML. Data was collected by using observation, interview, literature study, and distributing questionnaires involving 35 respondents. Measurement of data using a Likert scale, with correlation test analysis using Spearman rho. The implementation of a web-based prototype system with the results of the usability value test on the system application shows that the system has met the aspects of learnability, efficiency, memorability, errors, and satisfaction. The results of the correlation analysis of the Zachman Framework model on the system built have a very strong correlation, which implies that the system built through the Zachman Framework approach can be realized and implemented